E3 ubiquitin ligase OsPIE3 destabilises the B-lectin receptor-like kinase PID2 to control blast disease resistance in rice - Wang, Ke (The New phytologist, 2023)
© 2022 The Authors New Phytologist © 2022 New Phytologist Foundation.